Topological solitons stabilized by a background gauge field and soliton-anti-soliton asymmetry - Yuki Amari; Minoru Eto; Muneto Nitta (Journal of High Energy Physics, 2024)
Abstract We study topological lumps supported by the second homotopy group π 2(S 2) ⋍ ℤ in a gauged O(3) model without any potential term coupled with a (non)dynamical U(1) gauge field. It is known that gauged-lumps are stable with an easy-plane potential term but are unstable to expand if the model has no potential term. In this paper, we find that these gauged lumps without a potential term can be made stable by putting them in a uniform magnetic field, irrespective of whether the gauge field is dynamical or not. In the case of the non-dynamical gauge field, only either of lumps or anti-lumps stably exists depending on the sign of the background magnetic field, and the other is unstable to shrink to be singular. We also construct coaxial multiple lumps whose size and mass exhibit a behaviour of droplets. In the case of the dynamical gauge field, both the lumps and anti-lumps stably exist with different masses; the lighter (heavier) one corresponds to the (un)stable one in the case of the nondynamical gauge field. We find that a lump behaves as a superconducting ring and traps magnetic field in its inside, with the total magnetic field reduced from the background magnetic field.